Evaluasi dan Perancangan User Interface Aplikasi Mobile Layanan Pengaduan Masyarakat Online Menggunakan Human-Centered Design - Malik Abdul Azis; Hanifah Muslimah Az-Zahra; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Developing an e-Complaint application becomes one of the supporters of Open Government Indonesia implementation. Usability is one of the important aspects of application quality measurement. To support this, it is necessary to evaluate the e-Complaint interface so that people can comfortably use it. This research will evaluate two e-Complaint applications namely LAPOR! and Qlue. The evaluation was performed using usability testing supported by a USE questionnaire that included four parameters: usefulness, ease of use, ease of learning and satisfaction. Each of these parameters has several statements that will be given to the user to assess the usability level of the application. Preparation of improvement framework in this research is by using Human Centered Design (HCD), because at each stage of the research involves the user. Testing will be done twice, preliminary and final testing. Initial tests were performed to analyze the usability level of LAPOR! and Qlue. Then the final test is done to get the value of usability of the e-Complaint application recommendation design. Evaluation results on the LAPOR! application is in a â€œgood enoughâ€ category, Qlue is in a â€œgoodâ€ category but in the lower limit of the category, and the application design of the e-Complaint application is in a good category but exceeds the usability level of Qlue.